Validity of an instrument to evaluate the immunobiological cold chain - Maíla Martins Oliveira; Valéria Conceição de Oliveira; Ana Paula Ferreira; Ilka Afonso Reis; Heloísa de Carvalho Torres; Gabriela Gonçalves Amaral; Eliete Albano de Azevedo Guimarães (Universidad Nacional de Colombia, 2020)
Objective: To develop and to test the validity of content and layout of a multidimensional tool to evaluate maintenance of the cold chain for immunobiological conservation. Method: A methodological study carried out in three steps: integrative review; development of theoretical and logical model for the development of the tool; implementation of the Delphi Technique to test the validity of content and layout. The Content Validity Index (CVI) and Content Validity Ratio (CVR) were calculated considering appropriate those values greater than or equal to 75% and 0.4, respectively. Results: The instrument consisted of 7 questions about structure and 20 about process, subdivided into three components: Transportation/Reception (n=3); Storage/Handling (n=13); Supervision/Permanent education (n=4). The CVI value was 87.4%, with values equal to 85.7% and 89% in the structure and process dimensions, respectively. The process components obtained CVI values equal to 88.9, 88.9 and 89.2%, respectively. The CVR was 0.8, with values equal to 0.7 and 0.8 in the structure and process dimensions. As for the layout validation, the questionnaire was considered intelligible. Conclusion: The study provides an instrument with validity of content and layout for health professionals in charge of the supervision of activities of immunobiological conservation, ensuring the maintenance of the immunogenic quality of the products offered to the population.